Wypalenie rodzicielskie a podatność na ocenę społeczną - Włosiak, Julia; Sikorska, Iwona (Człowiek i Społeczeństwo, 2024)
Parental burnout, manifested by emotional distancing from the child, mental and emotional exhaustion, and a sense of futility in being a parent, is a phenomenon whose symptoms are increasingly reported by parents. The aim of the presented research was to identify the relationship between parents’ susceptibility to social assessment (fear of being negatively perceived) and the level of their parental burnout. The research participants were parents of children up to 7 years of age (N = 327), including 88% women. Subjects recruited using the snowball method were invited to answer a survey on the Google platform. The Polish Version of the Parental Burnout Assessment (PBA-PL), Social Inhibition Questionnaire (SIQ-15) and Sense of Negative Social Evaluation Scale were used to measure variables. In the study group, 5% of parents were observed to be in the area of high parental burnout and 15% in the area of risk, which is a high result when comparing to international data. The obtained findings indicate a weak, positive correlation between the level of parental burnout and multivariate social inhibition (r = .182; p < .001) and between the level of parental burnout and the sense of negative social evaluation (r = .278; p < .001). Lack of freedom in social relationships and susceptibility to negative evaluation by others are important for satisfaction with one’s own parenting competences.